Loss of Microglia and Impaired Brain-Neurotrophic Factor Signaling Pathway in a Comorbid Model of Chronic Pain and Depression - Zhu, Cuizhen; Xu, Jinjie; Lin, Yezhe; Ju, Peijun; Duan, Dongxia; Luo, Yanjia; Ding, Wenhua; Huang, Shengnan; Chen, Jinghong; Cui, Donghong (Frontiers in Psychiatry, 2018)
Major depressive disorder (MDD) and chronic pain are two complex disorders that often coexist. The underlying basis for this comorbidity is unknown. In the current investigation, microglia and the brain-derived neurotrophic factor (BDNF)-cAMP response element-binding protein (CREB) pathway were investigated. A comorbidity model, with characteristics of both MDD and chronic pain, was developed by the administration of dextran sodium sulfate (DSS) and the induction of chronic unpredictable psychological stress (CUS). Mechanical threshold sensory testing and the visceromotor response (VMR) were employed to measure mechanical allodynia and visceral hypersensitivity, respectively. RT-qPCR and western blotting were used to assess mRNA and protein levels of ionized calcium-binding adaptor molecule 1(Iba-1), nuclear factor-kappa B (NF-κB), nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκBa), BDNF, and CREB. In comorbid animals, mechanical allodynia and visceral hypersensitivities were significant with increased mRNA and protein levels for NF-κB-p65 and IκBa. Furthermore, the comorbid animals had deceased mRNA and protein levels for Iba-1, BDNF, and CREB as well as a reduced number and density of microglia in the medial prefrontal cortex (mPFC). These results together suggest that DSS and CUS can induce the comorbidities of chronic pain and depression-like behavior. The pathology of this comorbidity involves loss of microglia within the mPFC with subsequent activation of NF-κB-p65 and down-regulation of BDNF/p-CREB signaling.